1995
DOI: 10.1038/378279a0
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of the central executive system of working memory

Abstract: Working memory refers to a system for temporary storage and manipulation of information in the brain, a function critical for a wide range of cognitive operations. It has been proposed that working memory includes a central executive system (CES) to control attention and information flow to and from verbal and spatial short-term memory buffers. Although the prefrontal cortex is activated during both verbal and spatial passive working memory tasks, the brain regions involved in the CES component of working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
685
9
6

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,324 publications
(756 citation statements)
references
References 17 publications
56
685
9
6
Order By: Relevance
“…Moreover, they also indicate that similar prefrontal areas are activated by tasks requiring executive processes which at a first sight are quite different. For example, the middle prefrontal gyrus (BA 9/46) was found in manipulation [30,40,98] and updating [103,124] tasks as well as in dual-task coordination [39], inhibition processes [26,31] and shifting processes [102]. Furthermore, the activity of that region was directly linked to the memory load, as demonstrated by Braver et al [17] and Cohen et al [28] using parametric design studies.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Moreover, they also indicate that similar prefrontal areas are activated by tasks requiring executive processes which at a first sight are quite different. For example, the middle prefrontal gyrus (BA 9/46) was found in manipulation [30,40,98] and updating [103,124] tasks as well as in dual-task coordination [39], inhibition processes [26,31] and shifting processes [102]. Furthermore, the activity of that region was directly linked to the memory load, as demonstrated by Braver et al [17] and Cohen et al [28] using parametric design studies.…”
Section: Discussionmentioning
confidence: 83%
“…The first neuroimaging study which explored dual-task coordination was that of D'Esposito et al [39]. Participants were administered two tasks predominantly involving posterior brain regions and requiring no storage in working memory: a semantic judgement task (to identify exemplars of a target category in series of orally presented words) and a spatial-rotation task (to indicate which of two squares had a dot in the same location, relative to a double line, as a spatially rotated target square).…”
Section: Dual-task Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of these previous imaging studies suggested a specific role of the lateral prefrontal cortex (LPFC) for dual-task processing (D'Esposito, Detre, Alsop, Shin, Atlas, & Grossman, 1995;Goldberg et al, 1998;Schubert & Szameitat, 2003; but see Jiang, Saxe, & Kanwisher, 2004). Specifically, these studies compared the fMRI activation in dual-task blocks with the activation when participants performed the component tasks in single-task blocks, thereby employing the method of cognitive subtraction (Friston, Price, Fletcher, Moore, Frackowiak, & Dolan, 1996).…”
Section: Introductionmentioning
confidence: 99%